Synergistic Effect of HAD-B1 and Osimertinib Against Gefitinib Resistant HCC827 Non-Small Cell Lung Cancer Cells - Eun-Ju Ko KMD, PhD; Eun-Bin Kwag PhD; Ji-Hye Park KMD, PhD; Sung-Hyuk Cho MS; So-Jung Park KMD, PhD; Mi-Kyung Jung KMD, PhD; In-Cheol Kang PhD; Hwa-Seung Yoo KMD, PhD (Integrative Cancer Therapies)
In this study, we investigated the synergistic effect of co-administration of osimertinib and HAD-B1 using gefitinib-resistant non-small cell lung cancer cells, HCC827-GR. HAD-B1 is composed of 4 natural drugs, Panax Notoginseng Radix, Panax ginseng C. A. Meyer, Cordyceps militaris, and Boswellia carterii Birdwood, and has been reported to have therapeutic effects on patients with advanced non-small cell lung cancer in several studies. Resistance to gefitinib in HCC827 cells was acquired through MET activity. Co-treatment with osimertinib and HAD-B1 reduced the cell viability of HCC827-GR cells. In addition, phosphorylation of MET and ERK were effectively suppressed for HCC827-GR cells. And, compared to when osimertinib and HAD-B1 were administered alone, cell proliferation was significantly inhibited and apoptosis was effectively induced when osimertinib and HAD-B1 were co-administered to HCC827-GR cells. We found that the synergistic effect of osimertinib and HAD-B1 combination therapy resulted in cancer cell death and cell cycle arrest by targeting the ERK and mTOR signaling pathways. In conclusion, this study confirmed that the combination of osimertinib, a third-generation anticancer drug, and HAD-B1, a natural anticancer drug, had a potentially synergistic effect on non-small cell lung cancer resistant to EGFR-targeted anticancer drugs.